Chapter 3 Nothing as practical as an analytical strategy in realist evaluation - Nielsen, Steffen Bohni; Lemire, Sebastian (Taylor & Francis, 2024)
Realist Evaluation: Principles and Practice offers a comprehensive exploration of contemporary realist evaluation, showcasing how skilled practitioners navigate diverse fieldwork contexts. Authored by experts spanning academia and evaluation backgrounds across five continents in fields including climate change, criminology, health, and international development, the book provides a rich tapestry of perspectives. Covering participatory approaches, digital and visual data collection, interpreter-mediated interviews, and innovative methods like refuse data analysis, the authors delve into contemporary social research methodologies while addressing issues such as power, insider/outsider research, the nature of evidence, critical and scientific realism philosophies of science, and confirmation bias in qualitative research. Practical advice is provided in areas such as developing a topic guide, combining a realist review with an evaluation, and managing large, multi-site cross-national projects. This collection underscores the creative nature of the realist imagination, highlighting ongoing innovations by scholars and evaluators. With contributions from an outstanding group of internationally renowned experts in realist evaluation including Nick Tilley, a key figure in the development of realist evaluation alongside Ray Pawson, this is the ideal text for students, researchers and professionals including policy makers, professional evaluators, and those at organisations such as thinktanks and NGOs, who require an accessible guide on how to use realist evaluation methods.